Induction training programme of resident doctors: The need of the hour - Md Sameer; Jawahar S. K. Pillai; Biswajeevan Sahoo (Journal of Family Medicine and Primary Care)
Background: An induction training program is a structured process to acclimatize and orient the newly inducted staff or employees to an organization. As per the literature, there is no structured induction training program for resident doctors available in tertiary care teaching hospitals in India. Unlike other institutions, hospitals are complex places with several departments, processes, and patient services. Resident doctors in teaching medical institutions are a valuable human resource as they form the frontline doctors for delivering healthcare services. Therefore, the resident doctor needs to be oriented to the institution as early as possible to ensure quality in patient care services. The study aims to develop an induction training program for newly joined residents in teaching medical institutions and evaluate its effectiveness. The study setting was AIIMS, Bhubaneswar and the duration of the study was 6 months. Methodology: The ADDIE (analyze, design, develop, implement, and evaluate) model of human resource management was used as the study tool to develop the training program. An online national survey was conducted in the analyze phase to identify the training needs of residents. A comprehensive training module was developed based on the findings and referring the NABH Standards. The modules were implemented in a pilot mode in the study setting, and feedback was collected to understand the effectiveness of the program. Results: A training program for residents with 14 modules was developed and implemented. It consisted of 22 credits. The findings of the online survey and the feedback of the training program were found to be similar in many aspects though study participants were different in the analyze and evaluate phases. The Hospital Infection Control Practices, Hospital Management Information Systems, and Medico-legal Module were rated high by the residents. The study outlined the need for an induction training program for resident doctors in medical institutions. Based on the survey, the module was prepared and implemented. This module can be a model that can be replicated in other medical institutions. Conclusion: An induction training program for resident doctors was developed that helped them to get oriented to their workplace and improve their skills. This activity directly affects the quality of healthcare services thereby significantly contributing to patient safety.